2019
DOI: 10.1002/mbo3.874
|View full text |Cite
|
Sign up to set email alerts
|

Broad‐leaved forest types affect soil fungal community structure and soil organic carbon contents

Abstract: Evergreen broad‐leaved (EBF) and deciduous broad‐leaved (DBF) forests are two important vegetation types in terrestrial ecosystems that play key roles in sustainable biodiversity and global carbon (C) cycling. However, little is known about their associated soil fungal community and the potential metabolic activities involved in biogeochemical processes. In this study, soil samples were collected from EBF and DBF in Shennongjia Mountain, China, and soil fungal community structure and functional gene diversity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 63 publications
4
7
0
Order By: Relevance
“…In short, the present study demonstrates difference in soil microbial communities and soil properties between southern boreal forests in the Greater Khingan Mountains, China. It is consistent with the earlier findings 36,37 , and provide new evidence for the effects of tree species on soil communities and soil properties in southern boreal forest. The previous study documented that tree species showed a positive effect on soil C and N stocks in an Iranian temperate forest 38 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In short, the present study demonstrates difference in soil microbial communities and soil properties between southern boreal forests in the Greater Khingan Mountains, China. It is consistent with the earlier findings 36,37 , and provide new evidence for the effects of tree species on soil communities and soil properties in southern boreal forest. The previous study documented that tree species showed a positive effect on soil C and N stocks in an Iranian temperate forest 38 .…”
Section: Discussionsupporting
confidence: 92%
“…It has been also reported that soil bacterial community structure and function in German temperate deciduous forests were governed by the tree species 40 . Soil fungal communities also varied between Chinese subtropical evergreen and deciduous forests 37 . Those previous studies have confirmed that tree species contribute to differences in soil microbial communities and soil properties 41 .…”
Section: Discussionmentioning
confidence: 98%
“…The representatives of this genus are well-known late wood colonizers, that probably feed on the substrates which were decomposed by other organisms able to degrade complex substrates like cellulose ( Richardson, 2009 ). However, Umbelopsis representatives are also often isolated from living plant material or forest soil ( Sheng et al, 2019 ) and are considered to be plant growth-promoting organisms and root endophytes ( Tejesvi et al, 2013 ; Huang et al, 2015 ). They can alter plant metabolism leading to the enhanced production of complex metabolites which are not produced without the endophyte ( Qin et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The representatives of this genus are well-known late wood colonisers, that probably feed on the substrates which were decomposed by other organisms able to degrade complex substrates like cellulose [95]. However, Umbelopsis representatives are also often isolated from living plant material or forest soil [96] and are considered to be plant growth-promoting organisms and root endophytes [97,98]. They can alter plant metabolism leading to the enhanced production of complex metabolites which are not produced without the endophyte [99].…”
Section: Discussionmentioning
confidence: 99%